2002
DOI: 10.1161/01.res.0000019757.57344.d5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Improves Smooth Muscle Sarco/Endoplasmic Reticulum Ca 2+ -ATPase Function and Lowers Tyrosine Nitration in Hypercholesterolemia and Improves Nitric Oxide–Induced Relaxation

Abstract: Abstract-Antioxidants improve endothelial function in hypercholesterolemia (HC); however, whether this includes improvement of the vascular smooth muscle response to NO is unknown. NO relaxes arteries, in part, by stimulating Ca 2ϩ uptake via sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA) in aortic smooth muscle, and HC impairs SERCA function and the response to NO. HC induces oxidative stress, which could impair SERCA function. To study the effect of antioxidants, which are known to improve endothelium-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 55 publications
3
70
0
2
Order By: Relevance
“…Protein nitration can have a significant impact on the structural and functional integrity of the proteome (Sohal et al 2000;Murray et al 2003;Greenacre and Ischiropoulos 2001;Adachi et al 2002;Castro et al 1994;Gole et al 2000;Ischiropoulos 2003). Specific brain regions are especially vulnerable to oxidative stress as a result of elevated free radical levels and insufficient antioxidant defenses (Coyle and Puttfarcken 1993;Sohal et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Protein nitration can have a significant impact on the structural and functional integrity of the proteome (Sohal et al 2000;Murray et al 2003;Greenacre and Ischiropoulos 2001;Adachi et al 2002;Castro et al 1994;Gole et al 2000;Ischiropoulos 2003). Specific brain regions are especially vulnerable to oxidative stress as a result of elevated free radical levels and insufficient antioxidant defenses (Coyle and Puttfarcken 1993;Sohal et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…31 Briefly, sections (4 m thick) were deparaffinized, rehydrated, and treated with 10 mmol/L citric acid (pH 6.0). Sections were heated with a microwave (2 minutes, 3 times at 700 W) to recover antigenicity.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Not only does nitrotyrosine represent a marker of oxidative stress, but also the modification of protein structure can cause abnormal protein function. As examples, we have previously demonstrated that the nitration of MnSOD, prostacyclin synthase, and sarcoplasmic/reticulum calcium ATPase is associated with decreased enzyme activities (24,26,31). Furthermore, the marked improvement of renal function associated with S18886 is likely to be causally related to the dramatic improvement in tyrosine nitration observed.…”
Section: Discussionmentioning
confidence: 95%
“…The alkaline phosphatase reaction was stopped before any nonspecific staining occurred. Semiquantitative analysis of tissue immunoreactivity was done in a blinded fashion by trained medical research laboratory personnel using the arbitrary 0 -4 grading system previously described (26) to estimate the degree of overall staining on the kidney cross section. Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%